PENERAPAN METODE COOPERATIVE LEARNING MODEL STAD UNTUK PERBAIKAN KUALITAS PEMBELAJARAN DI JURUSAN TJP FT UNNES - Putri, Meddiati Fajri (Lembaran Ilmu Kependidikan, 2007)
This research is aimed to improve lecture quality of food hygiene and sanitationat TJP Boga of FT Unnes. At least 75% students got score seven for their mid test andat least 75% got score seven for final test. Research is conducted by applying 2research cycles consist of class discussion. There are 4 groups with a STAD studentand a lecturer in each group. The cycle consist of seven action. Most of students, i.e.66% got score above 70. Students are getting happier, more enthusiastic, active, andbrave, in lecturer.Kata kunci: Cooperative Learning, model STAD, kualitas pembelajaran